Intradermal hepatitis B vaccine in thalassaemia and sickle cell disease. Issue 4 (April 1989) - Mok, Q; Underhill, G; Wonke, B; Aldouri, M; Kelsey, M; Jefferies, D
Abstract : Thirty two patients with beta thalassaemia and sickle cell disease who were having regular blood transfusions were selected to test the efficacy and immunogenicity of low dose (2 micrograms or 0.1 ml) intradermal hepatitis B vaccine compared with the standard (20 micrograms or 1 ml) intramuscular dose. There was no significant difference in the rates of seroconversion, seroconversion had occurred in all patients by seven months. There were no significant differences in antibody titres between the intramuscular and intradermal groups at 1, 2, and 6 months. Although the titres were significantly higher in the intramuscular group at seven months and at 12-18 months, the antibody titre in the intradermal group did not fall below 10 IU/l. The results of this study suggest that low dose intradermal hepatitis B vaccination is an effective and economical way of stimulating an immune response in patients with beta thalassaemia and sickle cell disease.